(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of financial performance on the company’s market capitalization. Independent variables used in this study are financial performance, which consists of net profit margin (NPM) and earnings per share (EPS), while the dependent variable is market capitalization. The sample in this study consisted of 4 BUMN fields of construction listed on the Indonesia Stock Exchange in 2012–2017. They were selected based on specific criteria using the purposive sampling method. The method of data analysis used in this study is multiple linear regression. The results of simultaneous analysis showed that the NPM and EPS are simultaneously effects on market capitalization. and partially showed that only variables NPM had an effect on market capitalization, whereas EPS had no effect on market capitalization.